A novel cooling geometry for subsea variable speed drives. (25th February 2021) - Militão, Lucas A.; Fernandes, Caio D.; dos Santos, Diego; Machado, Douglas M.; Heldwein, Marcelo L.; Rambo, Carlos R.; da Silva, Alexandre K.; Barbosa Jr., Jader R.
Abstract: Experimental and theoretical analyses are conducted to evaluate the passive cooling performance of a novel geometry for subsea variable speed drives, a common piece of equipment in deep-sea oil exploration. Relying on the sea water as a low-temperature thermal reservoir, the new design forms an enclosed, annular space with centrally located modular boards that compose the power electronics inverter. Buoyancy-induced motion of a dielectric coolant conveys the heat dissipated by the electronic boards to the sea water through the outer and innermost walls of the annular enclosure. A thermal network model is implemented and used to optimize the enclosure geometry through a genetic algorithm, which served as a reference for a scaled experimental setup. A Computational Fluid Dynamics (CFD) simulation of the conjugate heat transfer yielded temperature distributions on the electronic boards and temperature and fluid velocity fields inside the enclosure. A comparison between the experimental data and the modeling results indicated a good agreement, with average RMS deviations of a modified Nusselt number of 7.0% and 8.5% for the thermal network and CFD analysis, respectively. For a 140-W operating point dissipation rate in the scaled test setup, the thermal network and the CFD models presented maximal deviations of 4°C and 2.3°C with respect to the heat sink temperature measurements. Highlights: Natural circulation cooling of a dielectric oil in an annular enclosure is studied. Experiment was designed based on a thermal network (TN) model and genetic algorithms. Oil velocities and circuit board temperature distribution were determined via CFD. TN and CFD predicted the Nusselt number with RMS deviations of 7.0% and 8.5% New geometry is a promising compact solution for subsea applications.